Exogenous Short Chain Fatty Acid Effects in APP/PS1 Mice - Zajac, Diana J.; Shaw, Benjamin C.; Braun, David J.; Green, Stefan J.; Morganti, Joshua M.; Estus, Steven (Frontiers in Neuroscience, 2022)
Elucidating the impact of the gut microbiome on Alzheimer’s Disease (AD) is an area of intense interest. Short chain fatty acids (SCFA)s are major microbiota metabolites that have been implicated as a mediator of gut microbiome effects in the brain. Here, we tested the effects of SCFA-treated water versus saline-treated water on APPswe/PSEN1dE9 mice maintained under standard laboratory conditions. Mice were treated with SCFAs from five months of age until ten months of age, when they were evaluated for microbiome profile, impaired spatial memory as evaluated with the radial arm water maze, astrocyte activation as measured by Gfap expression and amyloid burden as assessed by histochemistry and MSD ELISA. We report that SCFA treatment increased alpha-diversity and impacted the gut microbiome profile by increasing, in part, the relative abundance of several bacteria that typically produce SCFAs. However, SCFA treatment did not significantly affect behavior. Similarly, SCFAs did not affect cortical or hippocampal astrocyte activation observed in the APP/PS1 mice. Lastly, although robust levels of soluble and insoluble amyloid were present in the APP/PS1 mice, SCFA treatment had no effect on these indices. Overall, our findings are that SCFA treatment modifies the microbiome in a fashion that may increase further SCFA production. However, SCFA treatment did not alter behavior, astrocyte activation, nor amyloid neuropathology in APP/PS1 mice maintained with a conventional microbiome.